2008
DOI: 10.1002/cncr.23519
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 trial of talactoferrin in previously treated patients with metastatic renal cell carcinoma

Abstract: Dabrafenib is a small‐molecule inhibitor of BRAF kinase activity that is currently being developed for the treatment of BRAF V600 mutation‐positive melanoma. This clinical, open‐label, two‐cohort (n = 14 per cohort), randomized study was designed to evaluate the effect of drug substance particle size, and food on the plasma pharmacokinetics of a single oral dose of dabrafenib in patients with BRAF V600 mutation‐positive solid tumors. In addition, an exploratory cross‐cohort comparison of the relative bioavaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…Indications of anticancer activity were observed in both cancer types. Based on these results, follow-up phase II studies have been conducted with indications of anti-cancer activity in patients with both NSCLC [14][15][16] and RCC [17]. Talactoferrin is now in phase III clinical development for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Indications of anticancer activity were observed in both cancer types. Based on these results, follow-up phase II studies have been conducted with indications of anti-cancer activity in patients with both NSCLC [14][15][16] and RCC [17]. Talactoferrin is now in phase III clinical development for the treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…9) This multitude of biological activities has created great interest in the use of LF in drug discovery. 10) Recently, we have developed PEGylated LF with high biological activities and enhanced pharmacokinetics properties. 11) PEGylation refers to the modification of biological molecules by the linking of one or more polyethylene glycol (PEG) groups.…”
mentioning
confidence: 99%
“…NSCLC patients (n=12) experienced 87% relative reduction in TGR and renal cell carcinoma (RCC) patients (n = 7) experienced a 98% relative reduction in TGR [84]. In a phase 2 clinical trial of TLf in RCC, Jonasch et al [85] reported that TLf given at a dose of 1.5 g twice daily (12 weeks on, 2 weeks off) resulted in no toxicities to 44 patients with RCC, 6.4 months mPFS, 21.1 months median overall survival, and a 77% 1-year survival rate. The effect of orally administered bLF was also evaluated clinically in patients with ≤5 mm colorectal polyps.…”
Section: Lactoferrin and Lactoferricinmentioning
confidence: 97%